Effect of Aeration and Compaction on Some Characters Of a Turf Grass Mixture Under Sulamani City Conditions - Sharbazery, Ali Othman Mohammed; Gareeb, Berivan Abdulkhaliq (Sulaimani Journal for Pure and Applied Sciences, 2018)
This experiment was carried out in Perramagron area in the Northwestern part of Sulaimani city, at the Ornamental Plant Nursery , (Lebanon Mountain Company) for cultivation and landscape (35° 32' N, 45° 21' E, and 730m altitude), for the period 15th May 2012 to 1st September 2012to study the effect of aeration, without aeration, compaction and without compaction on same characters of turf grass mixture. The Factorial Experiment (2*2) was laid out by using the Complete Randomized Block Design (CRBD), Each treatment combination was replicated four times with plot (1×4) m2. Obtained results show that: aeration significantly caused increased in plant density, root depth, active root, and Soil infiltration when compared with non-aeration. But compaction 70 kg treatment decreased plant density, root depth, active root, and soil infiltration when compared with non-compaction. In contrast, the bulk density was increased significantly because of this treatment. The interaction between aeration and without compaction give the highest average of Plant density 640 plants/m2, root depth 53.00 cm root, active root 18 cm, highest level of Soil infiltration 1.08cm. While the highest Bulk density 1.95gm/cm3was recording in the treatment that aeration and compaction.
Keywords: Turf grass mixture; lawn aeration; Turf grasses soil compaction and aeration